A Novel Interleukin 33/ST2 Signaling Regulates Inflammatory Response in Human Corneal Epithelium - Lin, Jing (Public Library of Science, 2013)
Interleukin (IL) 33, a member of IL-1 cytokine family, is well known to promote Th2 type immune responses by signaling through its receptor ST2. However, it is not clear whether ST2 is expressed by mucosal epithelium, and how it responds to IL-33 to induce inflammatory mediators. This study was to identify the presence and function of ST2 and explore the role of IL-33/ST2 signaling in regulating the inflammatory cytokine production in corneal epithelial cells. Human corneal tissues and cultured primary human corneal epithelial cells (HCECs) were treated with IL-33 in different concentrations without or with different inhibitors to evaluate the expression, location and signaling pathways of ST2 in regulating production of inflammatory cytokine and chemokine. The mRNA expression was determined by reverse transcription and real time PCR, and protein production was measured by enzyme-linked immunosorbent assay (ELISA), immunohistochemical and immunofluorescent staining. ST2 mRNA and protein were detected in donor corneal epithelium and cultured HCECs, and ST2 signal was enhanced by exposure to IL-33. IL-33 significantly stimulated the production of inflammatory cytokines (TNF-α, IL-1β and IL-6) and chemokine IL-8 by HCECs at both mRNA and protein levels. The stimulated production of inflammatory mediators by IL-33 was blocked by ST2 antibody or soluble ST2 protein. Interestingly, the IκB-α inhibitor BAY11-7082 or NF-κB activation inhibitor quinazoline blocked NF-κB p65 protein phosphorylation and nuclear translocation, and also suppressed the production of these inflammatory cytokines and chemokine induced by IL-33. These findings demonstrate that ST2 is present in human corneal epithelial cells, and IL-33/ST2 signaling plays an important role in regulating IL-33 induced inflammatory responses in ocular surface.